Construction of recombinant Marek’s disease virus co-expressing σB and σC of avian reoviruses - Gao, Li; Zhong, Li; Liu, Yongzhen; Liu, Changjun; Zhang, Yanping; Cui, Hongyu; Qi, Xiaole; Zhang, Jiayong; Xu, Jia; Wang, Suyan; Chen, Yuntong; Duan, Yulu; et al. (Frontiers in Veterinary Science, 2024)
Avian reoviruses (ARVs) cause viral arthritis or tenosynovitis, resulting in poor weight gain and increased feed conversion ratios in chickens. In this study, we generated three Marek’s disease virus (MDV) recombinants, namely, rMDV-ARV-σB, rMDV-ARV-σC, and rMDV-ARV-σB + C, expressing ARV σB, σC, and both σB and σC, respectively. In rMDV-ARV-σB and rMDV-ARV-σC, the σB or σC gene was inserted into the US2 gene of MDV vaccine strain 814 using a fosmid-based rescue system. In rMDV-ARV-σB + C, the σB and σC genes were cloned into different expression cassettes, which were co-inserted into the US2 gene of the MDV 814 strain. In infected chicken embryo fibroblasts (CEFs), the recombinant virus rMDV-ARV-σB expressed σB, rMDV-ARV-σC expressed σC, and the rMDV-ARV-σB + C virus simultaneously expressed σB and σC. These recombinant viruses exhibited growth kinetics in CEFs similar to those of the parent MDV, and the inserted genes were stably maintained and expressed in the recombinant MDVs after 20 passages in cell cultures. These recombinant MDVs expressing σB and σC will provide potential vaccines against ARV infection in chickens.